2003
DOI: 10.2169/internalmedicine.42.1095
|View full text |Cite
|
Sign up to set email alerts
|

Different Risk Factors for the Maximum and the Mean Carotid Intima-media Thickness in Hemodialysis Patients

Abstract: ObjectiveHigh-resolution B-mode ultrasonography has been widely used for the noninvasive assessment of atherosclerosis in hemodialysis patients. But, there are two major methods of carotid ultrasonography: one inc luding plaque and the other excluding plaque.Methods The subjects were 112 hemodialysis patients (58 men and 54 women) with a mean age of 55.8±13.0 years. The maximum intima-media thickness (IMT) of the carotid artery (including plaque) was measured as an index of arterial wall thickening and atherom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
3
18
1
Order By: Relevance
“…Thus, MCSF, an important factor that functions at the cellular level, probably plays important roles in developing atherosclerotic changes in the carotid arteries of HD patients. As reported [16], SBP, DBP, and PTH were also associated with IMT. An increased carotid IMT in the present study was associated with the ischemic ECG changes which could be explained by the close relationship between atherosclerotic lesions in the coronary arteries and those in the carotid arteries reported by others [15].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, MCSF, an important factor that functions at the cellular level, probably plays important roles in developing atherosclerotic changes in the carotid arteries of HD patients. As reported [16], SBP, DBP, and PTH were also associated with IMT. An increased carotid IMT in the present study was associated with the ischemic ECG changes which could be explained by the close relationship between atherosclerotic lesions in the coronary arteries and those in the carotid arteries reported by others [15].…”
Section: Discussionsupporting
confidence: 71%
“…Ample evidence shows that an increase in carotid IMT is associated with important clinical outcomes such as ischemic stroke and cardiovascular accidents [15]. Different risk factors might be relevant to mean and maximum IMT [16]. Here, we report for the first time that MCSF is associated with an increase in both adjusted mean and maximum IMT.…”
Section: Discussionmentioning
confidence: 53%
“…Mast et al [17] collected data from two prospective studies and showed that smoking was significantly associated with highgrade carotid artery stenosis (> 60%), especially in white smokers who smoked 20 pack-years or more, and that this effect was independent of other risk factors. Regarding IMT, Nakashima et al [18] reported a positive correlation between maximum IMT and smoking in hemodialysis patients, but no correlation between mean IMT and smoking. They considered the possibility that mean IMT was related merely to arterial wall thickening, while maximum IMT was related to atheroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Relationships between free carnitine, SAF, and cIMT. SAF skin autoflourescence, cIMT carotid intima-media thickness when arteriosclerosis was assessed by the mean cIMT that reflected the arterial wall thickness [26]. However, the maximum cIMT was used to assess arteriosclerosis in the present study, which was known to reflect the arterial wall thickness and atheroma formation [26].…”
Section: Discussionmentioning
confidence: 89%
“…SAF skin autoflourescence, cIMT carotid intima-media thickness when arteriosclerosis was assessed by the mean cIMT that reflected the arterial wall thickness [26]. However, the maximum cIMT was used to assess arteriosclerosis in the present study, which was known to reflect the arterial wall thickness and atheroma formation [26]. The reason why no significant relationships were found between them is to adopt the values of systolic blood pressure and low-density lipoprotein cholesterol that were well controlled with medications and also to adopt the maximum cIMT for data analysis.…”
Section: Discussionmentioning
confidence: 99%